GO GOLD GENERATION WEB-BASED QUIZ FOR TEACHING AND LEARNING GRAMMAR IN SENIOR HIGH SCHOOL: RESEARCH AND DEVELOPMENT - Nurur Riszkasari; Dian Fadhilawati; Adin Fauzi (JOSAR (Journal of Students Academic Research), 2021)
This research aims to establish the Go Gold Generation (3G) Web-Based Quiz for teaching and learning grammar that focused on simple past tense, present perfect tense, and past continuous tense, to discover the appropriateness of 3G web-based quiz for teaching and learning grammar, and to find out the teachers’ and students’ responses toward the use of 3G web-based quiz for teaching and learning grammar to the tenth-grade students. The researchers adapted Sugiyono’s research and development framework as a reference. The adaption has been formulated into three phases, which were: foundational research; design and development; and perception test and finalization. The research result showed that the validation score was 89,73% included in the “Very Valid” category. The result of teachers’ and students’ responses score was 89,09% included in the “Very Good” category. It means that a 3G web-based quiz can be applied as an alternative media for teaching and learning grammar to the tenth-grade students in senior high school. Furthermore, the final product of the model consisted of 3G Web-Based Quiz, guidebooks for teachers and students, and assessment guidelines.